A 3-D finite element study of the influence of crown-implant ratio on stress distribution - Moraes, Sandra Lúcia Dantas de; Verri, Fellippo Ramos [UNESP]; Santiago, Joel Ferreira [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Mello, Caroline Cantieri de [UNESP]; Pellizzer, Eduardo Piza [UNESP] (FapUNIFESP (SciELO), 2013)
The purpose of this study was to assess the influence of the crown height of external hexagon implants on the displacement and distribution of stress to the implant/bone system, using the three-dimensional finite element method. The InVesalius and Rhinoceros 4.0 softwares were used to generate the bone model by computed tomography. Each model was composed of a bone block with one implant (3.75 x 10.0 mm) with external hexagon connections and crowns with 10 mm, 12.5 mm and 15 mm in height. A 200 N axial and a 100 N oblique (45°) load were applied. The models were solved by the NeiNastran 9.0 and Femap 10.0 softwares to obtain the results that were visualized by maps of displacement, von Mises stress (crown/implant) and maximum principal stress (bone). The crown height under axial load did not influence the stress displacement and concentration, while the oblique loading increased these factors. The highest stress was observed in the neck of the implant screw on the side opposite to the loading. This stress was also transferred to the crown/platform/bone interface. The results of this study suggest that the increase in crown height enhanced stress concentration at the implant/bone tissue and increased displacement in the bone tissue, mainly under oblique loading.
Keywords: Finite element analysis; Dental prosthesis; Implantsupported; Biomechanics; Dental implants